The Impact of the COVID-19 Pandemic on Alzheimer's Disease and Other Dementias - Gan, Jinghuan; Liu, Shuai; Wu, Hao; Chen, Zhichao; Fei, Min; Xu, Junying; Dou, Yuchao; Wang, Xiaodan; Ji, Yong (Frontiers in Psychiatry, 2021)
Introduction: Numerous countries went into lockdown to contain the COVID-19 outbreak, which has impeded follow-up of chronic diseases, such as cognitive impairment (CI). Cognitive and neuropsychiatric changes during the COVID-19 pandemic are neglected in China, which is the world’s whistleblower. To investigate the cognitive and neuropsychologic changes in CI, as well as the proportions of rapid cognitive decline (RCD) before and during the COVID-19 pandemic to provide clinical evidence for CI intervention during a public health emergency. Methods: We performed a descriptive and retrospective study based on medical records from the memory clinic of Tianjin Dementia Institute collected through face-to-face evaluations. Information of 205 patients with CI, including patients with mild cognitive impairment and dementia, of whom 131 with Alzheimer’s disease (AD) were analyzed and compared to a control group before the COVID-19 pandemic. Results: Among the 205 CI patients, the scores on the Chinese Mini Mental State Examination (C-MMSE), the Montreal Cognitive Assessment (MoCA), activities of daily living (ADLs), and the global Neuropsychiatric Inventory (NPI) were significantly different at the baseline and follow-up evaluations (p < 0.05) after 14.07 (±2.87) months. The same findings were recorded among AD patients, and they exhibited more sleep disturbances at the follow-up than at baseline (32.8% vs. 20.6%, p = 0.035). When compared to the control group, slightly worse performance of cognitive, −1.00 (−4.00, 1.00) from the C-MMSE, −1.00 (−2.00, 0.00) on the MoCA, 1.00 (0.00, 9.00) on ADLs and neuropsychological 0.00 (−1.00, 3.50) on the global NPI profile, at the follow-up were presented, particularly for delusion, agitation, irritability, and appetite disturbances (p < 0.05). Twenty-five (19.1%) AD patients and 48 (36.6%) controls suffered RCD during the COVID-19 pandemic. Moreover, AD patients during the COVID-19 pandemic were 0.408 times (95% confidence interval: 0.232–0.716) less likely to suffer RCD than the control. Conclusion: Confinement might ease the cognitive and neuropsychiatric deterioration of AD patients compared to those not in crisis and help prevent RCD in AD patients.